2006
DOI: 10.1634/stemcells.2005-0580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging and Niche Microenvironment on Spermatogonial Stem Cell Self-Renewal

Abstract: Aging is evident in most tissues and organ systems, but the mechanisms of aging are difficult to identify and poorly understood. Here, we test the hypothesis that aging results in uncorrected defects in stem cell and/or niche function, which lead to system failure. We used the spermatogonial stem cell (SSC) transplantation assay to determine the effect of aging on testis stem cell/niche function in mice. Between 12 and 24 months of age, male mice experienced a declining level of fertility associated with decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
194
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(207 citation statements)
references
References 30 publications
11
194
0
2
Order By: Relevance
“…The gradual loss of the differentiated touch dome lineage over weeks suggests that neural signals are important in the self-renewal of touch dome stem cells but are dispensable for differentiation of existing stem cells. That microenvironmental signals can prevent the exhaustion of somatic stem cells has been observed in other organs with respect to aging (28)(29)(30). Our results show a similar failure of stem cell maintenance when neural Shh is removed from the touch dome microenvironment.…”
Section: Discussionsupporting
confidence: 82%
“…The gradual loss of the differentiated touch dome lineage over weeks suggests that neural signals are important in the self-renewal of touch dome stem cells but are dispensable for differentiation of existing stem cells. That microenvironmental signals can prevent the exhaustion of somatic stem cells has been observed in other organs with respect to aging (28)(29)(30). Our results show a similar failure of stem cell maintenance when neural Shh is removed from the touch dome microenvironment.…”
Section: Discussionsupporting
confidence: 82%
“…Many of these signals and cross-talk between the somatic cells and stem cells are still unknown, although it is evident that some, like GDNF, have essential roles in embryonic development and are not restricted to the testis. In addition, recent work has demonstrated that the decline in spermatogenesis with aging reflects a degradation of the stem cell niche, rather than defects inherent to the stem cells (Ryu et al, 2006). Therefore, a thorough understanding of the niche and its experimental modulation may help devise new treatments for male infertility or possibly lead to the development of novel male contraceptives.…”
Section: Resultsmentioning
confidence: 99%
“…The physical wearing of the niche areas has been shown to affect stem cell properties, too: in mice, thinning of the subventricular zone, a neurogenic stem cell niche, has been associated with decrease of cell proliferation and neuroblast numbers (Luo et al 2006). Moreover, declining mouse testis weight with age has also been linked to reduction in levels of spermatogenesis (Ryu et al 2006). In the same manner, the physical reduction and wear of the limbal niche after the age of 60 could be correlated to the decelerated wound healing clinically observed in that age group, including the delayed corneal epithelial wound healing after injury or infections such as microbial keratitis or following surgery such as corneal keratoplasty (Constantinou et al 2009;Parmar et al 2006;Ibrahim et al 2009;van der Meulen et al 2008).…”
Section: Discussionmentioning
confidence: 99%